RANCANG BANGUN SISTEM KEAMANAN BRANKAS MENGGUNAKAN E-KTP DAN RFID (RADIO FREQUENCY IDENTIFICATION) BERBASIS NODEMCU ESP8266 - Zidni, Syafa'atu; Rakhmadi, Frida Agung; Putra, Agfianto Eko (Prodi Fisika Fakultas Sains dan Teknologi UIN Sunan Kalijaga Yogyakarta, 2021)
Safe is a tool used to store goods or assets and securities. Generally, a safe uses an analog lock made of metal and a rotary combination lock as a security system. However, the existing safe is not equipped with an information system that will notify the owner when the safe is accessed. This research was developed a safe security system using a digital key in e-KTP form which is detected by RFID (Radio Frequency Identification) sensor and the system was equipped with an information system based on nodeMCU ESP8266 to send notifications. The system designed consists of RC522 RFID module used to detect the e-KTP ID of the safe accesser. RFID connected to the nodeMCU platform which is an IoT device and connected to the cloud via wifi ESP8266. The information contained in the cloud from the IoT device and forwarded to the receiving smartphone as notification.